A CHALLENGING CASE: SPINAL CORD SARCOIDOSIS. Issue 10 (9th September 2014) - Wynford-Thomas, Ray; Smith, Philip
Abstract : A 54-year old man with severe ankylosing spondylitis presented with rapidly progressing bilateral lower limb weakness and altered sensation, associated with urinary retention. Examination showed flaccid paraparesis with lower limb areflexia and a sensory level to T10. His upper limbs were normal. MR scan of whole spine showed marked ankylosing spondylitis changes, including canal narrowing, and extensive, discontinuous signal change within the spinal cord at C7–T1, T3–T4 and T7–T11. There was no leptomeningeal enhancement. Severe ankylosing spondylitis meant we were unable to obtain CSF, MR scan of head or do a leptomeningeal biopsy (anaesthetic risk). CT scan of thorax however showed extensive mediastinal and hilar lymphadenopathy. We could therefore obtain a tissue diagnosis from lymph node biopsy, which showed sarcoid-type, non-caseating granulomas. We diagnosed neurosarcoidosis and prescribed immunosuppression. His paraplegia is unchanged, but his neurology is stable. Spinal cord sarcoidosis is rare (<1%) but treatable and must be considered as a differential diagnosis of spinal cord lesions. Diagnosis however can be difficult due to unusual radiological findings and was made more challenging here by the addition of ankylosing spondylitis. Histological confirmation is often the key to diagnosis, as in this case.